Provincial Administration in Babylonia: A Case of Kassite Nippur - Redina-Thomas, Marina (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
The talk gives an overview of the system of provincial administration in Babylonia during the rule of the Kassite dynasty (ca. 1531-1155 BC). Since about 90% of all written sources from this period (almost 12000 cuneiform tablets) come from a single location – the city of Nippur, the religious center of the country – this study is based for the most part on the economic and administrative documents from that place. The available texts cover about 150 years – from the beginning of the reign of Burna-Buriaš II (ca. 1359 B.C.) till the end of the reign of Kaštiliashu IV (1225 B.C.). The documents reflect the vibrant economic life of the region and give some ideas about how the social organization of Nippur and settlements of the homonymous adjacent province was shaped and how the city administrative system functioned. They mention administrators and officials of different levels responsible for the city household transactions (record keeping of economic accounts, maintaining agricultural and irrigational activities, distributing the harvest and goods, supervising the workforce). Among them one official clearly stands out – the chief governor of Nippur (šandabakku in Akkadian, gú.en.na/gá.dub.ba.(a) in Sumerian). He probably reported directly to the king of Babylonia and was endowed with significant political and administrative power, controlling economic transactions in the region and performing legal procedures. Several persons holding šandabakku office also bear a title nešakku (nu.èš den.líl in Sumerian) – one of the important priest offices of the god Enlil’s temple – Ekur. That indicates that the governor of Nippur was closely linked to the largest city temple and was involved in the governance and administration of its household as well.